STATE BENEFITS AND REQUIREMENTS OF STATE DOCUMENTATION OF LANDS (American Journal of Technology and Applied Sciences, 2025)
The article sets out a number of new requirements for the legalization of rights to illegally occupied land plots and buildings and structures erected on them, and also provides new benefits to landowners and the termination of illegal occupation. A brief overview of scientific research on the provision of benefits in relation to illegally occupied land plots and buildings and structures constructed on them in the Republic of Karakalpakstan is presented.